2015
DOI: 10.1080/10543406.2015.1092038
|View full text |Cite
|
Sign up to set email alerts
|

Development of Statistical Methods for Analytical Similarity Assessment

Abstract: To evaluate the analytical similarity between the proposed biosimilar product and the US-licensed reference product, U.S. Food and Drug Administration (FDA) statisticians collaborated with Chemistry, Manufacturing and Control (CMC) scientists at FDA in order to develop a three-tier approach. The proposed tiered approach starts with a criticality determination of quality attributes (QAs) based on their potential impact on product quality and the clinical outcomes. Those QAs characterize the biological product i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 2 publications
1
33
0
Order By: Relevance
“…4,6 This is done using 2 simultaneous 1-sided tests to analyze the composite null and alternative hypotheses (H 0 and H 1 , respectively), which are: H 0 : μ ≤ θ L or μ ≥ θ U (the treatment difference is outside the equivalence margin) and H 1 : θ L < μ < θ U (the treatment difference is within the margins), where θ L and θ U are the lower and upper margins, respectively, and μ is the analysis criterion (eg, mean ratio or mean difference). 4,9,10 This is done with 2 sets of hypotheses (H a0 : μ ≤ θ L with H a1 : μ > θ L and H b0 : μ ≥ θ U with H b1 : μ < θ U ). 4,9 The H 0 is rejected in favor of H 1 if the CI for μ is contained completely within the range (θ L –θ U ).…”
Section: Terminology and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6 This is done using 2 simultaneous 1-sided tests to analyze the composite null and alternative hypotheses (H 0 and H 1 , respectively), which are: H 0 : μ ≤ θ L or μ ≥ θ U (the treatment difference is outside the equivalence margin) and H 1 : θ L < μ < θ U (the treatment difference is within the margins), where θ L and θ U are the lower and upper margins, respectively, and μ is the analysis criterion (eg, mean ratio or mean difference). 4,9,10 This is done with 2 sets of hypotheses (H a0 : μ ≤ θ L with H a1 : μ > θ L and H b0 : μ ≥ θ U with H b1 : μ < θ U ). 4,9 The H 0 is rejected in favor of H 1 if the CI for μ is contained completely within the range (θ L –θ U ).…”
Section: Terminology and Definitionsmentioning
confidence: 99%
“…3 Instead, biosimilars are evaluated in a stepwise fashion that includes structural and functional studies, nonclinical assessments of pharmacokinetics (PK) and toxicity, and clinical evaluation of PK, efficacy, and safety (including immunogenicity) to demonstrate similarity of the potential biosimilar to the originator biologic. 1–4 Approval of a potential biosimilar is based on the totality of the evidence in demonstrating similarity of the biosimilar to the reference product. 1–4 Totality of the evidence refers to the extensive comparative structural, functional, nonclinical, and clinical data required to establish biosimilarity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has raised a number of debatable (controversial) issues in analytical similarity assessment (see also (6,7)). These issues include, but are not limited to, (1) fundamental similarity assumption, (2) primary assumptions for tiered approach, (3) statistical properties of FDA's recommended Tier 1 equivalence test, (4) criticism of fixed approach for margin/range selection, (5) inconsistencies between tired approaches, (6) sample size requirement, (7) heterogeneity within lots and across lots within and between test product and reference product, (8) interpretation of FDA's current thinking on scientific input, (9) relationship between similarity limit and variability, and (10) a proposed unified tiered approach.…”
Section: Introductionmentioning
confidence: 99%
“…For the analytical studies, FDA suggests that CQAs should be identified and classified into three tiers according to their criticality or risk ranking based on mechanism of action (MOA) or PK using appropriate statistical models or methods. CQAs with CQAs that are most relevant to clinical outcomes will be classified to Tier 1, while CQAs that are less (mild-tomoderate) or least relevant to clinical outcomes will be classified to Tier 2 and Tier 3, respectively (4,5).…”
Section: Introductionmentioning
confidence: 99%